ROLE MODEL KEBIJAKAN PEMBERANTASAN PENYALAHGUNAAN NARKOTIKA DI KOTA PEKANBARU - Zulfa Harirah MS; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Circulation and abuse of drugs in Pekanbaru city show significant improvement. Based on data from the Drug Investigation Division Police Directorate Riau dan Resta Pekanbaru, cases of drug abuse in Pekanbaru city in 2011 there were 72 cases with 94 suspects, in 2012 there were 79 cases with 115 suspects, and in 2013 as of October there were 102 cases with 129 suspects. Formulation of the problem in this research is how to role model appropriate policies in combating drug abuse in Pekanbaru city, so the purpose of this research is to find a role model of appropriate policies in combating drug abuse in the city of Pekanbaru.This research is a qualitative research with deskriptif method. This research was done through observation, in-depth interviews, Focus Group Discussion and documentation. Techniques of data analysis done by data reduction, organizing the data, and interpretation of data. The results of this research show that the efforts made by BNN Pekanbaru city of prevention, empowerment, and eradication have not been able to minimize of drug abuse cases in Pekanbaru city, although the value of the BNN gains of Pekanbaru city average in 2012 is 119% and in 2013 is 112,97%. So the role models offered to combat drug abuse is back to the Malay identity by combining the values of the indigenous Malay culture and religious values.Keywords: Role models, narcotics, policy